ANALISIS ASIMILASI KULTURAL ETNIS MELAYU DAN JAWA DI DESA MEKAR SEKUNTUM KECAMATAN TEBAS KABUPATEN SAMBAS - Melinda Melinda; Rustiyarso Rustiyarso; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The general problem in this research is how is the process of assimilate the ethnic Malay and Javanese culture in Mekar Sekuntum Village, Tebas District, Sambas Regency?. The sub-problems of this research was how the Cultural Assimilation of Livelihoods, Social Organization, and Language of the Malays and Javanese in Mekar Sekuntum Village?. The research methode used was a qualitative approach with descriptive methods. The informants were the ethnic Malay and Javanese couple, Mr, M and Mrs. R and Mr. S and Mrs. U. R. The result showed that every informant had been assimilated by means of a livelihood, where after maariage they changed their job as an electronic mechanic, entrepreneur, construction worker, paud honorarium, and rice farmer. In terms of social organization, each pair of their children follows from the woman’s parent (mother), the marriage custom is carried out bassed on the mutual agrrement of each couple. In terms of language each pair of different ethnic Malays and Javanese has shown that there has been assimilation. Keywords: Cultural Assimilation, Ethnic Malay and Javanese